Kontroversi Di Ketinggian Kontroversi di Ketinggian Analisis Framing Pemberitaan Hilangnya Iphone dalam Penerbangan Garuda - Endang Susilomurti; Gita Mahyarani (Pusat Riset dan Inovasi Nasional, 2025)
This study examines how Indonesian media framed the viral incident of a lost iPhone aboard Garuda Indonesia's flight GA716 (June 2025), applying Pan & Kosicki's framing model to analyze five news outlets. The research identifies three dominant frames: system failure (Kumparan), legal professionalism (Kompas.com), and class conflict (Poskota). Findings reveal how media narratives have shaped the public's perception of corporate accountability, with Garuda's crisis response oscillating between transparency and defensiveness. The study bridges framing theory with crisis communication (Coombs, 2007) and reputation management (Fombrun, 1996), highlighting the tension between media sensationalism and corporate image control in the digital age. Practical implications suggest that airlines must integrate real-time media monitoring with proactive reputation management strategies.